ksar Boukais in Béchar, its reality and preservation mechanisms - Bekaddour, meryem (Journal of Social Sciences and Humanities, 2025)
The desert areas were known and characterized by the architecture of traditional clay palaces, which inspired many scholars interested in studying the architectural heritage of such areas.desert palaces are a city that pulsates with many religious, customary and social values and a sincere expression of the local community adhering to its customs, traditions and values, despite the abandonment of many children and grandchildren for various circumstances to modern housing, but they are still witnessing a set of activities and the visit of many tourists. all this and that requires study in order to preserve and value such material heritage in the desert areas of Algeria. In order to study such a cultural heritage, we will highlight the boukais Palace, one of the palaces of the north, along with the mougul and lahmar in the state of Bechar in Algeria, which was distinguished by its architecture and its watering and water distribution system, which surprised many researchers, and its customs and traditions, to personalize its current reality, especially since parts of it were demolished and obliterated due to neglect, and we propose a set of solutions that contribute to some extent to preserve and value it in light of the Algerian state's policy aimed at exploiting architectural heritage as an important tourist resource in activating desert tourism and preserving authenticity, since a physical witness of a historical epoch that marked such societies in the midst of the world's cultural diversity .